Direct Invasion of the Optic Nerves, Chiasm, and Tracts by Cryptococcus neoformans in an Immunocompetent Host. (October 2015) - Merkler, Alexander E.; Gaines, Nathan; Baradaran, Hediyeh; Schuetz, Audrey N.; Lavi, Ehud; Simpson, Sara A.; Dinkin, Marc J.
Cryptococcus spp is a common fungal infection and frequent cause of meningitis in immunocompromised patients; however, immunocompetent patients are also at risk of infection. Visual loss often occurs via elevated intracranial hypertension but can rarely occur through direct optic nerve, chiasm, or tract invasion. We report a case of a 38-year-old woman who presented with decreased acuity in both eyes. She had generalized visual field constriction in the right eye and temporal hemianopsia in the left eye. Magnetic resonance imaging of the brain and orbits showed multiple areas of ill-defined enhancement in the optic chiasm and tracts as well as in the diaphragmatic sella, prepontine and interpeduncular cisterns, and along cranial nerves VI, VII, and VIII bilaterally. Initial cerebrospinal fluid (CSF) showed 34 white blood cells, hypoglycorrhachia, and negative cryptococcal antigen and bacterial and fungal cultures. A transphenoidal biopsy of the dura and pituitary gland was unremarkable. Empiric steroids resulted in marked improvement in visual acuity in both eyes, but while tapering steroids, she developed rapid visual loss bilaterally. Repeat CSF performed 6 weeks later demonstrated a cryptococcal antigen titer of 1:512. Retroactive staining of the pituitary biopsy was positive for mucicarmine, a component of the polysaccharide capsule of Cryptococcus spp. After induction therapy with amphotericin B and flucytosine and 1 year of fluconazole, her visual acuity was 20/20 in both eyes. In summary, Cryptococcus can affect immunocompetent patients and often presents with insidious, chronic meningitis. Visual loss is common in cryptococcal meningitis but usually results from fulminant papilledema related to elevated intracranial pressure. In rare cases, direct nerve or chiasm infiltration by the fungus results in vision loss.